Satisfaction Survey of Occupational Medicine Residents During an External Rotation in the Medical Services of a Multinational Banking Company in Madrid, Spain A Cross-Sectional Study - Reinoso-Barbero, Luis; Fernández Álvarez-Rementeria, Arturo; Castillo-Sabogal, Andrea-Catherine; Muñoz-Dueñas, Pilar; Gómez-Paredes, Laura; Pérez-Herreras, Cristina; Gutiérrez-Aguiló, María; Muñoz-Gutiérrez, Juan; Gómez-Gallego, Félix; Martínez-Jarreta, Begoña (Journal of Occupational and Environmental Medicine, 2026)
The aim of this study was to describe satisfaction survey results from occupational medicine residents. Methods: Cross-sectional study with 10 closed-ended questions scored 1 to 10 and one open question. The survey was given to 52 residents during a one-month external rotation in the Medical Services of a multinational company in Madrid, Spain. Results: 31 residents were physicians (59.6%) and 39 were women (75%). 13 residents (25%) did not complete the survey. Closed-ended questions scored ≥9. The lowest scores were rotation time, mean 9.0, and achievement of objectives, mean 9.3. 33 residents answered the open question. Of these, 81.8% expressed gratitude. Suggestions included extending rotation (27.3%) and rotating with senior occupational risk prevention technicians, SORPT (21.2%). Conclusions: Satisfaction amongst residents was high. It is proposed to increase rotation time and ensure all residents rotate with SORPT.
Keywords: occupational medicine; residents; postgraduate education